SPACE LAW - THE NEW SUB-BRANCH OF LAW STUDIES IN LATVIA - Grasis, Janis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Latvia became an associate member of the European Space Agency (ESA) in 2020. The ESA is an intergovernmental organisation dedicated to the exploration of space. According to the Article II of the Convention of establishment of a European Space Agency, the purpose of the ESA is to promote, for exclusively peaceful purposes, cooperation among European States in space research and technology and their space applications, with a view to their being used for scientific purposes and for operational space applications systems. “The Space Strategy for Latvia 2021-2027” (Strategy) recently was collectively developed by the Ministry of Education and Science and the Ministry of Economics of the Republic of Latvia. It establishes a focused framework for the cooperation of Latvia with the ESA and contributes to the achievement of the objectives, priorities and actions defined in the Latvian National Development Plan 2021-2027, the National Industrial Policy Guidelines 2021-2027 and the Science, Technological Development and Innovation Guidelines 2021-2027. As it is indicated in the Strategy, Latvian higher education institutions ensure the development of an adequate base of expertise and skills in graduates to be able to serve the needs of the space sector in Latvia. It is proposed in Strategy that Universities in collaboration with local industrial partners develop higher-education courses and lifelong learning programmes to respond to the national space industry need. Novelty of the research: this is one of the first academic research concerning the possible studies of space law in the Latvian higher education institutions. Just now law studies are provided by 8 higher education institutions; but no one offers single study course on space law. The research aim is to analyse necessity to teach space law in the universities of the Republic of Latvia, taking into account the fact that Latvia now is an associate member of the ESA. The author has used descriptive, analytical and deductive-inductive research methods in the article. After review and analysis of the legal acts, policy planning documents and different reports, the author has made conclusions and recommendations. Preliminary it seems that space law must be teached as separated study course (or at least this topic must be included in the study course “International air law” or similar study course); publication of teaching book “Space law” also is desirable in latvian language.